2014
DOI: 10.1175/jpo-d-13-07.1
|View full text |Cite
|
Sign up to set email alerts
|

Coastal-Trapped Waves in the East China Sea Observed by a Mooring Array in Winter 2006

Abstract: Using five mooring array observations in the coastal water of the East China Sea (ECS) in winter 2006, the authors identify three kinds of low-frequency waves using the ensemble empirical mode decomposition (EEMD) method. The analysis indicates that the periods of the waves varied from 2 to 10 days, which are consistent with coastal-trapped wave (CTW) modes: the Kelvin wave (KW) mode, the first shelf wave (SW1) mode, and the second shelf wave (SW2) mode. An analytical model is established and the dispersion re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 32 publications
3
27
0
Order By: Relevance
“…The SSH and current responses to synoptic winter wind in the BYES have been recognized to be energetic based on data from several coastal tide gauge stations (Chen & Su, ; Ding et al, ; Hsueh & Romea, ; Yin et al, ) and some in situ current observations (Hsueh, ; Huang et al, ; Lin et al, ; Li et al, ; Teague & Jacobs, ; Yin et al, ). However, the basin‐scale SSH and current variations have not yet been fully revealed, possibly due to the limited spatial and temporal coverage of the observed data and the lack of an effective method to decompose the overall variations into several leading modes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SSH and current responses to synoptic winter wind in the BYES have been recognized to be energetic based on data from several coastal tide gauge stations (Chen & Su, ; Ding et al, ; Hsueh & Romea, ; Yin et al, ) and some in situ current observations (Hsueh, ; Huang et al, ; Lin et al, ; Li et al, ; Teague & Jacobs, ; Yin et al, ). However, the basin‐scale SSH and current variations have not yet been fully revealed, possibly due to the limited spatial and temporal coverage of the observed data and the lack of an effective method to decompose the overall variations into several leading modes.…”
Section: Discussionmentioning
confidence: 99%
“…The bottom topographies and wind conditions facilitate the generation of CTWs in the BYES in winter. In fact, CTWs in the BYES have been observed with both tidal gauge data (Chen & Su, ; Hsueh & Romea, ; Yin et al, ) and TOPEX/POSEIDON altimeter satellite data (Jacobs, ; Jacobs, Preller, et al, ; Jacobs, Teague, et al, ). These studies have confirmed that CTWs with dominant periods of 2–10 days propagate southward and northward along the Chinese and Korean coasts, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The EMD scheme was used in studying sea level rise (Ezer et al, 2013). Yin et al (2014) also applied the method and identified three kinds of low-frequency waves using some observations in the coastal water of the East China Sea.…”
Section: Empirical Mode Decompositionmentioning
confidence: 99%
“…Schmitt et al [10] applied the HHT method to characterize the scale invariance of velocity fluctuations in the surf zone. Ying et al [11] applied the method and identified three kinds of low-frequency waves using some observations in the coastal water of the East China Sea. The EMD scheme has also been used in studying sea level rise [12].…”
Section: A Brief Description Of Hhtmentioning
confidence: 99%